Reacting to the entry of green manufacturers: A perspective from ordinary manufacturers - Zhang, Linghong; Yu, Wenchao (Frontiers in Environmental Science, 2023)
More and more green manufacturers are entering the market, which poses a challenge to ordinary manufacturers as to whether they must produce environmental products. Motivated by competition between green manufacturers and ordinary manufacturers, this study examines how an ordinary manufacturer that produces a traditional product (product 1) adapts its product portfolio to compete with a new-entrant green manufacturer. The sale period is divided into two periods. In period 1, the green manufacturer enters the market and provides one green product (product 2). Subsequently, the ordinary manufacturer decides whether to develop a green product (product 3) in period 2. The products are differentiated in two characteristics: traditional quality and environmental quality. We derive the demand function by comparing the consumer utility obtained from the three products. Then, we investigate the ordinary and green manufacturers’ optimal decisions using game theory. Furthermore, we study how government subsidy of green products affects the two manufacturers’ decisions. Finally, we extend our model to discuss the market position of the two green produc2ts when the green technology level is fixed for two manufacturers. Our study suggests that 1) the ordinary manufacturer may not introduce the green product when the difference in environmental quality between two green products is much larger; 2) government subsidy is effective in stimulating the ordinary manufacturer to introduce green product, especially when the traditional manufacturer could provide high-environmental-quality product; and 3) the manufacturer’s green technology level and green technology maturity, and consumers’ willingness to pay for traditional quality, together affect product position.